Bias voltage optimization and cutting performance of AlCrN coatings deposited by a hybrid technology. (October 2022) - Fan, Qixiang; Zhang, Shuo; Ma, Dezheng; Wu, Zhenghuan; Cao, Fengting; Liu, Yanmei; Wang, Tiegang
Abstract: AlCrN coatings have been studied extensively by arc ion plating or magnetron sputtering, while there are scarce reports on the AlCrN coatings prepared by a hybrid technology of arc ion plating and magnetron sputtering. In this paper, five AlCrN coatings were prepared by the hybrid technology under bias voltages from −40 V to −200 V. XRD, SEM, TEM and nano-indenter etc. were used to study the microstructure and properties of the coatings. Results show that all the five coatings possess fcc-(Al, Cr)N phase with preferential orientation of (111) crystal plane. With higher bias voltage, the quantity of micro-particles decreases and the coating's surface quality is improved. Compressive stress, hardness and elastic modulus of the AlCrN coatings increase firstly and then decrease. The AlCrN coating with bias voltage of −160 V possesses the highest hardness about 33.2 GPa and lowest wear rate about 1.47 × 10 −6 mm 3 /N‧m. The cutting time of the AlCrN coated cutter deposited at −160 V is 2.4 times longer than that of the uncoated milling cutter, with H13 die steel as work-piece. The AlCrN coated cutter fails mainly due to abrasive and adhesive wear. In addition, oxidation and inter-diffusion between substrate/coating/workpiece also occur in the cutting zone. Highlights: Five AlCrN coatings are deposited by a hybrid technology under various bias voltages. Surface quality and mechanical properties are enhanced by the hybrid technology. The coating deposited at −160 V possesses the highest hardness and wear resistance. Cutting time of AlCrN coated cutter is 2.4 times longer than that of the bare cutter. AlCrN coated cutter fails mainly due to abrasive and adhesive wear.